A companion to film noir - Spicer, Andrew, 1953-; Hanson, Helen (Chichester, West Sussex : Wiley Blackwell, 2013)
"An authoritative companion that offers a wide-ranging thematic survey of this enduringly popular cultural form and includes scholarship from both established and emerging scholars as well as analysis of film noir's influence on other media including television and graphic novels. Covers a wealth of new approaches to film noir and neo-noir that explore issues ranging from conceptualization to cross-media influences Features chapters exploring the wider 'noir mediascape' of television, graphic novels and radio Reflects the historical and geographical reach of film noir, from the 1920s to the present and in a variety of national cinemas Includes contributions from both established and emerging scholars "--
"Film noir fascinates cineastes like no other genre. This authoritative companion features the work of a highly distinguished group of international scholars, adopting a thematic approach that examines key topics rather than focusing on individual titles or auteurs. It reflects the expanding purview of analysts by including novel subjects such as neo-noir, international noir movies, and 'noir' as expressed in other forms such as comics, graphic novels, posters, radio and television. Informed by cutting-edge scholarship, this collection extends and deepens the developing understanding of this enduringly captivating mode of cultural expression"--
pt. 1. Conceptualizing film noir -- pt. 2. Hidden, hybrid, and transmedia histories and influences -- pt. 3. Social, industrial, and commercial contexts -- pt. 4. The fabric of film noir : style and performance -- pt. 5. Identities and film noir -- pt. 6. Noir in other forms -- pt. 7. New geographies of film noir.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed July 23, 2013).
Keywords: Film noir -- History and criticism; PERFORMING ARTS -- Film & Video -- History & Criticism; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- Reference; Film noir; Detective and mystery stories -- History and criticism; Film noir -- History and criticism; Motion pictures; World War, 1939-1945 -- Motion pictures and the war; Electronic books; Criticism, interpretation, etc; Electronic books